The Transformation of The Concept of God for The Karo Catholic Tribe Will Be Dibata Sikaci-Kaci - Tibo, Paulinus; Bere, Paulus Hakek; Tinambunan, Edison RL. (International Journal of Indonesian Philosophy & Theology, 2024)
Karo people believe in the existence of Dibata Kaci-kaci (“God”). The understanding and belief about Dibata is obtained through life experiences, natural phenomena, and events experienced. The orientation of this research is to find the transformation of belief in Dibata as the concept of God for Karo Catholics. The research method used is qualitative, with interview techniques based on experiences derived from oral traditions, group discussion forums, and documentation. Research informants: five traditional leaders, two Karo culturalists, two priests, and five pastoral councils of parishes and stations. This research uses Rudolf Otto's (1917) theory of religious phenomenology to understand the experience and understanding of the sacred or numinous. This theory helps explain how Karo people experience and understand God's presence through natural phenomena and life events. The findings of this study are in line with previous research by Singarimbun (1975) and Ginting (2018), which also examined the concept of God in Karo beliefs. However, this study provides a new perspective by exploring the transformation of the concept in the context of Karo Catholics. The novelty of this research lies in finding the intersection between the experience and understanding of God in the beliefs of the Karo people and the concept of the Trinity in the teachings of the Catholic Church. The results show that the Karo people recognize, acknowledge, and believe in the existence of a God who is both transcendent and immanent, namely Dibata Datas (God Above), Dibata Tengah (God Middle), and Dibata Teruh (God Below). The experience and understanding of God in the Karo people's beliefs find common ground, thus becoming an opportunity for evangelization. The concept of the Karo God as a God with three persons (Dibata si Telu Sada) reveals the Karo belief that Dibata is present in all realities: the upper world, the middle world, and the lower world. For example, Karo: Mula jadi (creator, origin), Dibata Kaci kaci (loving God), Nini (grandfather). This finding is a new idea that can be used as catechetical material about the Trinity that the Catholic Church believes in.